2020
DOI: 10.7150/jca.48426
|View full text |Cite|
|
Sign up to set email alerts
|

TGF-β1-Induced Upregulation of MALAT1 Promotes Kazakh's Esophageal Squamous Cell Carcinoma Invasion by EMT

Abstract: Transforming growth factor β1 (TGF-β1) plays an important role in tumor initiation and development by inducing epithelial-mesenchymal Transition (EMT). Metastasis-Associated Lung Adenocarcinoma Transcript 1 (MALAT1) is a long noncoding RNA (lncRNA) that contributes to the invasion and metastasis of tumors, including esophageal squamous cell carcinoma (ESCC). The aim of the present study was to explore the underlying mechanisms implicated in EMT and to clarify whether TGF-β1 regulates MALAT1 expression, thereby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Recent studies have revealed that EMT exerts crucial roles in the invasion as well as metastasis of ESCC 30 . Nevertheless, the underlying mechanisms associated with EMT remain confusing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed that EMT exerts crucial roles in the invasion as well as metastasis of ESCC 30 . Nevertheless, the underlying mechanisms associated with EMT remain confusing.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that EMT exerts crucial roles in the invasion as well as metastasis of ESCC. 30 Nevertheless, the underlying mechanisms associated with EMT remain confusing. This investigation verified that the supression of EPPK1 significantly inhibits EMT progression, which indicates that EPPK1 might influence cell migration and invasion by mediating EMT.…”
Section: Discussionmentioning
confidence: 99%
“…In the tongue squamous cell carcinoma, MALAT1 could promote EMT while inhibit the apoptosis by regulating the activity of Wnt/β‐catenin pathway 33 . Of note, MALAT1 knockdown inhibited the EMT in TGF‐β1‐induced esophageal squamous cell carcinoma 34 . Consistently, the down‐regulation of MALAT1 could block the EMT of EC cells, with down‐regulations of Vimentin and SNAIL and the up‐regulation of E‐cadherin, indicating that the down‐regulation of MALAT1 could be a therapeutic target to inhibit the metastasis and invasion of EC.…”
Section: Discussionmentioning
confidence: 96%
“…This provides an evidence for a positive correlation between MALAT1 and EMT induction in CTCL cells because upregulation of epithelial marker with simultaneous downregulation of mesenchymal marker is reliable indication of reversal of EMT. The EMT induced by lncRNAs plays an important role in cancer metastasis ( 19 ) and accordingly MALAT1-induced EMT has been reported to regulate cancer metastasis ( 13 , 20 , 21 ). Thus, MALAT1 upregulation in CTCL can be related to a more aggressive disease.…”
Section: Discussionmentioning
confidence: 99%